(untitled) (Research, Society and Development, 2023)
The nursing teacher is exposed to several stressors, y can have a negative emotional experience caused by the imbalance between the needs of work and their responsiveness and, as a consequence, present the Burnout Syndrome (BS). Objective of the study was to identify the causes and consequences of BS in nursing teachers. This is an integrative literature review, whose articles were selected through the Portal de Publicações Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) and in the Redib, Dialnet, BDENF, EBSCO and PsycINFO databases, published from 2017 to October 2022. The final sample resulted in 28 articles, with level of evidence IV. In educational institutions, as the main causes of BS were pointed out: pedagogical interference, poor working conditions, weaknesses in interpersonal relationships, multifunctionality, work overload and difficulty adapting to virtual modality in times of COVID-19. In those inherent to the individual, the predominant causes were: those who had less resilience and had work addiction. Younger permanent teachers with more degrees are the most affected. Among the complications generated, the following stood out: affected mental health, sleep disorders and imbalance in personal-professional life. It is concluded that the occupational stressor was the cause of greater preponderance for BS and the impacts generated had a negative impact on physical and mental health, on the quality of teaching, besides provoking the intention to abandon the teaching career.